URGENSI POLA ASUH ANAK DALAM KELUARGA DI ERA GLOBALISASI - Agus Hermawan (INJECT (Interdisciplinary Journal of Communication), 2018)
Parenting in a family should be parents’ effort in nurturing and guiding children for both psychological and biological aspect since they were born to adulthood (18 years). It aims to develop self-control for children enhance they remain on a good and right pathway through a sets of teaching, guiding, mentoring and and self-controlling. Parenting should be understood by parents to enable them to looking after their children well. There are two significant elements of parenting style, the so-called: (1) parental responsiveness (parents’ response) and (2) parental demandingness (parents’ demand), while there are several parenting patterns in a family such as: democratic, authoritarian, and permissive pattern. AbstrakPola asuh anak dalam keluarga merupakan usaha orang tua dalam membina anak dan membimbing anak baik jiwa maupun raganya sejak lahir sampai dewasa (18 tahun). Tujuannya adalah untuk menciptakan kontrol diri pada anak agar tetap di jalan yang baik dan benar secara normal melalui serangkaian usaha pengajaran, bimbingan dan arahan serta pengontrolan diri. Pola asuh anak harus dipahami oleh orang tua agar mampu mengasuh anaknya dengan baik. Pola asuh memiliki dua elemen penting yaitu: (1) parental responsiveness (respons orang tua) dan (2) parental demandingness (tuntutan orang tua), sedangkan pola asuh anak dalam keluarga ada beberapa hal yaitu: pola demokrasi, pola otoriter, dan pola permisif.